ANALISIS STRUKTUR MODAL DAN NILAI TAMBAH ( ECONOMIC VALUE ADDED ) SUATU STUDI PADA PT BANK MUAMALAT Tbk - Liviawati Liviawati; Gusmarila Eka Putri; Hardi Hardi (Komunitas Manajemen Kompetitif, 2026)
Bank Muamalat was the first Islamic bank established in Indonesia. At the time of its inception, Bank Muamalat performed very well, even becoming the largest bank in Indonesia. Following the global crisis, one of the causes of which was COVID-19, Bank Muamalat's performance declined. To improve Bank Muamalat's performance, the government planned to acquire Bank Muamalat through Bank BTN. However, the planned acquisition of Bank Muamalat by Bank BTN was not implemented because, according to news obtained by the author from kompas.com in September 2024, Bank BTN switched to Bank Victory Syariah for acquisition. As a result, Bank Muamalat had to seek new investors to obtain additional funds to improve its performance. Based on the results of a study by researchers entitled